2017
DOI: 10.1210/en.2017-00566
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoids Suppress the Browning of Adipose Tissue via miR-19b in Male Mice

Abstract: Physiological levels of glucocorticoids (GCs) are required for proper metabolic control, and excessive GC action has been linked to a variety of pandemic metabolic diseases. MicroRNA (miRNA)-19b plays a critical role in the pathogenesis of GC-induced metabolic diseases. This study explored the potential of miRNA-based therapeutics targeting adipose tissue. Our results showed that overexpressed miR-19b in stromal vascular fraction (SVF) cells derived from subcutaneous adipose tissue had the same effects as dexa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
20
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 23 publications
2
20
1
1
Order By: Relevance
“…Earlier studies have indicated that glucocorticoid-induced obesity is secondary to a repressed expression of the brown fat-specific protein UCP1 and an ensuing decrease in thermogenesis (van den Beukel et al, 2015;Lv et al, 2018;Strack et al, 1995;Viengchareun et al, 2001). In the present investigation, we have examined the significance of UCP1 for the development of glucocorticoid-induced obesity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier studies have indicated that glucocorticoid-induced obesity is secondary to a repressed expression of the brown fat-specific protein UCP1 and an ensuing decrease in thermogenesis (van den Beukel et al, 2015;Lv et al, 2018;Strack et al, 1995;Viengchareun et al, 2001). In the present investigation, we have examined the significance of UCP1 for the development of glucocorticoid-induced obesity.…”
Section: Discussionmentioning
confidence: 99%
“…The exact mechanisms behind the development of obesity and obesity-related diseases in response to high levels of glucocorticoids are not known. However, an involvement of brown adipose tissue (BAT), the main site for non-shivering thermogenesis in most mammals, has been discussed (van den Beukel et al, 2015;Liu et al, 2013;Lv et al, 2018;Strack et al, 1995;Viengchareun et al, 2001). Normally, upon activation by the sympathetic nervous system in response to cold exposure or certain diets, BAT produces heat through the tissue-specific mitochondrial uncoupling protein 1 (UCP1) that uncouples substrate oxidation from ATP production and dissipates the proton gradient across the inner mitochondrial membrane as heat (Cannon and Nedergaard, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Despite a number of in vitro studies suggesting an important role of the GR in both white and brown adipose tissue differentiation and cell function [11,23,[30][31][32], more recent studies have revealed that the absence of the GR in WAT is dispensable for WAT differentiation and function in vivo [4,9,33]. In this respect, our genetic loss-of-function study now addresses a key question in the field of BAT research and GR-dependent endocrine control of metabolism by demonstrating that in contrast to previous assumptions, the GR in BAT is largely dispensable for systemic energy homeostasis during both short and long-term metabolic adaptations.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, certain studies find that glucocorticoids enhance, rather than suppress, insulin actions in human primary adipocytes [ 26 , 27 ]. Finally, glucocorticoids have been shown to repress the thermogenic activity of brown and beige adipocytes in rodents [ 28 31 ]. However, recent studies show that acute glucocorticoid exposure enhances the thermogenic activity of human brown adipose tissue [ 32 ].…”
Section: Introductionmentioning
confidence: 99%